Where is (Is there a?) Main Central Thrust in the NW Himalayas of Pakistan? - Spencer, David A. (Journal of Nepal Geological Society, 1995)
The term "Main Central Thrust" was first introduced into Himalayan terminology in 1939. Still today, much discussion exists about whether the Main Central Thrust is actually one, two or three thrust surfaces, especially in the Central Himalaya of India and Nepal. As the Main Central Thrust is widely accepted as the intracontinental thrust that separates the Higher and Lesser Himalaya, its recognition is therefore implicit in using these unit names in the Pakistan Himalaya. The location of any "Main Central Thrust" in the Pakistan area of the Northwest Himalayan region is likely to remain controversial for some time. This is simply because the area where the Main Central Thrust was last seen, to the south of the Kashmir Basin, was some 100 km away from the next suggested location in Neelum and Kaghan Valleys. This intervening area between the last known location and any new suggested location is only scantily mapped in part. Eleven suggestions of locations of the "Main Central Thrust" have been made in Pakistan and a review of their indicative features is given for discussion. Only one position of the Main Central Thrust, at Batal in the Kaghan Valley, is generally accepted by the majority of northwest Himalayan workers (who do believe in a continuation of the MCT) as the correct location for a major tectonic contact which might correlate with the Main Central Thrust.